Per una nuova filosofia della cittadinanza - Caruso, Sergio (Lectio Magistralis, 2014)
After reviewing the development of "citizenship" under a historical and conceptual profile, as well as the many faces of this concept under a philosophical and analytical profile, the author discusses his belief that a generalized and extended idea of "citizenship" could be the core of a new philosophical and political paradigm, even more so, and better, than the inevitably abstract idea of "justice": exactly what contemporary societies need. Especially because, although we have become citizens in the public sphere of the state, we have remained subjects in the face of both public and private powers governing our lives in civil society, on all levels: local, national, European, global. To this end, the author advises reconsidering the subjective qualification we used to call "citizenship" as a bundle of functions: not only the elector-citizen in the stricto sensu political sphere, but also the producer-citizen, the reproducing and educating citizen, the consumer-citizen, the saver-citizen, the taxpayer-citizen, the user-citizen, the resident-citizen, and so on. Notwithstanding political democracy, for each of these functions it is possible, as well as necessary, to find new forms of representative democracy returning to the citizens the powers and the "voice" which they currently seem to be stripped of.